Microwave-assisted, ruthenium-catalyzed intramolecular amide-alkyne annulation for the rapid synthesis of fused tricyclic isoquinolinones1. Issue 84 (16th September 2015) - Swamy, T.; Maheshwar Rao, B.; Yadav, J. S.; Ravinder, V.; Sridhar, B.; Subba Reddy, B. V.
<x xml:space="preserve">Abstract</x> Microwave accelerated synthesis of tricyclic isoquinolinones has been accomplished through a domino C–C and C–N bond formation by an intramolecular C–H activation.